2015
DOI: 10.1039/c4cp04812a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shape biaxiality on the phase behavior of colloidal liquid-crystal monolayers

Abstract: We extend our previous work on monolayers of uniaxial particles [J. Chem. Phys. 140, 204906 (2014)] to study the effect of particle biaxiality on the phase behavior of liquid-crystal monolayers.Particles are modelled as board-like hard bodies with three different edge lengths σ 1 ≥ σ 2 ≥ σ 3 , and use is made of the restricted-orientation approximation (Zwanzig model). A density-functional formalism based on the fundamental-measure theory is used to calculate phase diagrams for a wide range of values of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The isotropic-nematic phase transition of hard ellipses corresponds to a planar nematic-biaxial nematic phase transition of the oblate ellipsoids. Here we note that our present work can be considered as an extension of our previous studies done for monolayers of uniaxial and biaxial hard particles using restricted-orientation approximation [39,40].…”
Section: Introductionmentioning
confidence: 72%
“…The isotropic-nematic phase transition of hard ellipses corresponds to a planar nematic-biaxial nematic phase transition of the oblate ellipsoids. Here we note that our present work can be considered as an extension of our previous studies done for monolayers of uniaxial and biaxial hard particles using restricted-orientation approximation [39,40].…”
Section: Introductionmentioning
confidence: 72%
“…Moreover, the formation of mesophases was further rationalized in terms of the particle shape biaxiality θ which can be calculated as 33 : where two aspect ratios are κ 1 = L / T and κ 2 = W / T , respectively. θ varies from −1 (uniaxial platelike geometry), via 0 (i.e., L / W = W / T , perfect biaxiality), to 1 (uniaxial rodlike geometry) 34 . Specifically, rodlike colloids with less noticeable biaxial shape ( θ > 0.05) were stabilized in SmAu phase, as they can rotate freely along the L -axis because of the relatively small energy barriers for their rotation within layers.…”
Section: Resultsmentioning
confidence: 99%
“…This is largely due to the limited access to high-quality colloids with the inherent biaxial shape. Currently available biaxial colloids include bent silica rod 28 , goethite 29 , hectorite 30 , and lead carbonate boardlike particles 31 with unique D 2h symmetry 32 34 , of which goethite particles are mostly studied. These goethite colloids, however, show very broad polydispersity (up to 55%) in size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…6 The stability of this N B phase was ascribed to the particles' quasi self-dual shape, a geometry in between oblate and prolate, and to their significant size dispersity, which hinders the formation of the Sm phase. This key work has reignited recent interest, sparking numerous theoretical, experimental and computer simulation studies on hard board-like particles (HBPs) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and other biaxial geometries. 24,[28][29][30][31][32] Theoretical and computational studies on monodisperse systems have suggested that self-dual-shaped particles exhibit a higher tendency to form biaxial nematics.…”
mentioning
confidence: 99%